2014
DOI: 10.1007/s10151-014-1234-9
|View full text |Cite
|
Sign up to set email alerts
|

Extended lateral pelvic sidewall excision (ELSiE): an approach to optimize complete resection rates in locally advanced or recurrent anorectal cancer involving the pelvic sidewall

Abstract: Patients with locally advanced and recurrent cancer involving the lateral pelvic sidewall may be rendered suitable for potentially curative radical resection with a modification in the approach to the lateral pelvic sidewall. Our pilot series seems to indicate that our novel technique (ELSiE) is feasible, safe and yields high rates of complete pathological resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…An alternative approach has been recently described by the St Mark’s group[69]. It involves an initial transgluteal approach to the sciatic notch which is performed with patient in prone position.…”
Section: Surgical Approach Based On Location Of Diseasementioning
confidence: 99%
“…An alternative approach has been recently described by the St Mark’s group[69]. It involves an initial transgluteal approach to the sciatic notch which is performed with patient in prone position.…”
Section: Surgical Approach Based On Location Of Diseasementioning
confidence: 99%
“…The St. Marks group has described their extended lateral pelvic sidewall excision experience of six R0 resections for sidewall recurrences. 29 The authors describe two phases of dissection: the extrapelvic phase and the abdominal phase. The patient is initially placed prone, and dissection is continued down to the gluteal muscles.…”
Section: Pelvic Sidewall Recurrencesmentioning
confidence: 99%
“…The level of vascular division is dependent on whether or not the superior gluteal artery is sacrificed. 29…”
Section: Pelvic Sidewall Recurrencesmentioning
confidence: 99%
“…Shaikh et al recently reported a case series of six highly selected patients undergoing a novel extended lateral pelvic sidewall excision procedure for either primary or recurrent rectal or anal cancer, each achieving an R0 resection. 63 , 64 This standardized technique comprises an extra-pelvic phase and an abdominal phase that converge on the sciatic notch from either side, allowing en bloc resection of tumor. Half of the patients required excision of the sciatic nerve due to tumor involvement, and all patients had the internal iliac vessels ligated either above or below the level of the superior gluteal artery.…”
Section: Introductionmentioning
confidence: 99%